Perilaku Konsumsi Berkelanjutan di Sektor Wisata Kuliner pada Generasi Milenial: Model SCB-Cube - Mufidah, Aisyah Wahyu; Sijabat, Riris Amelia; Haryanto, Handrix Chris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sustainable consumption behavior, particularly in the culinary tourism sector, is one of the consumption behaviors that can be practiced in efforts to maintain the sustainability of human life and nature in the future. The purpose of this study is to examine the dynamics of sustainable consumption behavior in the culinary tourism aspect among millennials aged 25–34 years using the Sustainable Consumption Behavior (SCB-Cube) model. The research method used is a qualitative case study involving 4 Respondents who meet the criteria of being aged 25-34 years and have visited the Warung Betawi H. Jaja location more than 3 times. Data collection was conducted through face-to-face and online interviews to examine the dynamics of sustainable consumption behavior among Respondents based on the aspects and stages of the SCB-Cube Model. The research results indicate that the economic aspect still has a significant influence on the dynamics of Respondents' sustainable consumption behavior across various stages, including the selection, use, and disposal stages. Meanwhile, regarding the social and environmental aspects, not all Respondents incorporated them into their consumption behavior stages. Additionally, beyond the existing aspects, the influence of emotional attachment plays a crucial role in consumers' decisions during the disposal stage of consumption.